Discharge based processing systems for nitric oxide remediation - Hashim, S.A.; Wong, C.S.; Abas, M.R.; Dahlan, K.Z. (Penerbit Universiti Kebangsaan Malaysia, 2010)
An electron beam (EB) flue gas test rig and a dielectric barrier discharge (DBD) reactor were tested for the removal of nitric oxide (NO) from gas stream in separate experiments. In both systems, energised electrons were used to produce radicals that reacted with the pollutants. The EB system was a laboratory scale test rig used to treat emission from a diesel run generator. At 1.0 MeV and 10 mA more than 90% NO removal from flue gases flowing at 120 Nm(3)/h can be achieved. For higher removal percentage, higher beam current was required. In a related effort, a table top, two tubes DBD reactor was used to process bottled gases containing 106 ppm NO. Total removal (>99%) was achieved when the inlet gas contained only NO and N(2). Additional SO(2) in the in let gas stream lowered the removal rate but was overcame by scaling up the system to 10 DBD tubes. The system was operated with input AC voltage of 35 kV peak to peak. In the EB treatment system, the amount of NO(2) increased at high beam current, showing that the NO was also oxidised in the process. Whereas in the DBD reactor, the amount of NO(2) remained insignificant throughout the process. This leads to the conclusion that the DBD reactor is capable of producing total removal of NO. This is highly desirable as post treatment will not be necessary.